2022
DOI: 10.1037/adb0000758
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of high-intensity drinking and implications for intervention.

Abstract: Efforts to intervene with subgroups at particularly high risk for alcohol use require information on factors that differentiate drinking intensity levels. This article summarizes existing research and provides new findings on sociodemographics and risk factors that differentiate high-intensity drinking (HID) to provide context for developing and delivering interventions for the highest-risk drinkers. Cross-sectional data were obtained in 2019 from participants who reported past 30-day alcohol use in 2018 as pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 75 publications
2
15
0
1
Order By: Relevance
“…On the other hand, among the reasons for consumption, BD female university students allude to social motives, followed by coping with depression, and enhancement motives. The importance they give to social and enhancement motives for consumption supports the results of other studies in which most university students report that they drink for social and fun reasons ( Patrick et al, 2021 ; Richards et al, 2021 ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…On the other hand, among the reasons for consumption, BD female university students allude to social motives, followed by coping with depression, and enhancement motives. The importance they give to social and enhancement motives for consumption supports the results of other studies in which most university students report that they drink for social and fun reasons ( Patrick et al, 2021 ; Richards et al, 2021 ).…”
Section: Discussionsupporting
confidence: 83%
“…Despite this, research has focused more on extracting predictive models of the influence of coping and enhancement motives, indicating that they are more stable over time and that they are associated with a greater presence of negative consequences. Motives of a more external nature such as social is left out ( Cooper et al, 2016 ) despite being the most present among university students ( Patrick et al, 2021 ; Richards et al, 2021 ). The present study reinforces the importance of contemplating social motives, given that the higher the score in this type of motives, the greater the probability of BD, unlike the more internal reasons (coping and enhancement) in which this relationship is not so evident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los resultados indican que una gran porción de los participantes presenta patrones problemáticos de consumo de alcohol (i.e., consumo episódico elevado) y que, incluso, un porcentaje relativamente alto de los estudiantes presenta consumo extremo de alcohol (patrón de consumo característico de una de las clases de consumo identificadas). Apenas recientemente el consumo extremo de alcohol está adquiriendo notoriedad en el campo de investigación de las conductas de consumo (Hua et al, 2020;Patrick et al, 2021). En función de los presentes resultados, consideramos que las medidas de consumo extremo de alcohol (8/10 unidades estándar para mujeres y hombres, respectivamente) deberían incluirse de manera rutinaria en los estudios que analizan el consumo de alcohol y, además, deberían destinarse más esfuerzos a la identificación de sus posibles causas y consecuencias a corto, mediano y largo plazo.…”
Section: Discussionunclassified
“…Involvement in fraternity and sorority life and athletics, perceptions of intense academic demands, and peer influences and pressure have also been linked to heavy and problematic alcohol use (NIAAA, 2021). In this special issue, Patrick et al (2021) identified numerous risk factors for high-intensity drinking (HID; 8+/10+ drinks in a sitting for college women and men, respectively) such as certain drinking motives, mental health symptoms, and perceived norms for HID, among college students who drink. Research on college students also indicates that excessive drinking is associated with increased risk for stopping out or dropping out of college, as well as problems transitioning from college to graduate school or to the workforce (Arria et al, 2018).…”
mentioning
confidence: 99%